2020
DOI: 10.21203/rs.3.rs-44189/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TNF inhibitors exert a “hidden” beneficial effect in the cardiovascular lipoprotein profile of RA patients

Abstract: BACKGROUND: Higher cardiovascular risk has been largely described in rheumatoid arthritis as well as different effects of biologic agents in theses patients. The aim of present study is to analyze the effects of tumor necrosis factor inhibitors (TNFi) in the lipoprotein profile of rheumatoid arthritis (RA) patients using a broad laboratory assessment including a large number of no routine testsMETHODS: RA patients treated with and without TNFi were cross-sectionally compared regarding a broad spectrum of lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…[24][25][26] HDL functions are also impaired as a result of cytokines such as TNFα increased in RA, causing HDL to become pro-atherogenic and proinflammatory. 22 As far as we know, in our study, dysfunctional HDL levels determined by measuring the MPO/PON1 ratio were shown in RA patients for the first time.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…[24][25][26] HDL functions are also impaired as a result of cytokines such as TNFα increased in RA, causing HDL to become pro-atherogenic and proinflammatory. 22 As far as we know, in our study, dysfunctional HDL levels determined by measuring the MPO/PON1 ratio were shown in RA patients for the first time.…”
Section: Discussionsupporting
confidence: 53%
“…It has been reported that the levels of PON1 enzyme, which is the main antioxidant molecule of HDL, 22 can decrease in RA. 27 Similarly, in our study, it was observed that the PON1 activity was significantly lower in RA patients than the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation